2006
DOI: 10.1001/archpsyc.63.10.1158
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Posttraumatic Stress Disorder With Venlafaxine Extended Release

Abstract: In this study, venlafaxine ER was effective and well tolerated in short-term and continuation treatment of patients with posttraumatic stress disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 32 publications
(49 reference statements)
0
110
0
2
Order By: Relevance
“…A recent review of PTSD pharmacotherapy indicated that the largest and greatest number of trials showing efficacy have been with the SSRIs (Ipser and Stein, 2012). Venlafaxine, an SNRI, has had positive results in two trials with more than 800 participants with non-combat related PTSD (Davidson, Baldwin, et al, 2006;Davidson, Rothbaum, et al, 2006). PTSD practice guidelines from the Society for Traumatic Stress Studies and the American Psychiatric Association echo the recommendations of the VA/DoD CPG (American Psychiatric Association, 2004;Benedek et al, 2009;Foa, Keane and Friedman, 1999).…”
Section: Research Evidencementioning
confidence: 99%
“…A recent review of PTSD pharmacotherapy indicated that the largest and greatest number of trials showing efficacy have been with the SSRIs (Ipser and Stein, 2012). Venlafaxine, an SNRI, has had positive results in two trials with more than 800 participants with non-combat related PTSD (Davidson, Baldwin, et al, 2006;Davidson, Rothbaum, et al, 2006). PTSD practice guidelines from the Society for Traumatic Stress Studies and the American Psychiatric Association echo the recommendations of the VA/DoD CPG (American Psychiatric Association, 2004;Benedek et al, 2009;Foa, Keane and Friedman, 1999).…”
Section: Research Evidencementioning
confidence: 99%
“…Based on the proposed network model of LC-NE changes in the pathophysiology of anxiety and depression, findings from the preclinical studies and treatment efficacy studies suggest that blocking or attenuating the hyperactive NE system resulting from acute and repeated traumatic stress would be beneficial (e.g., the use of a1 antagonist, b blocker, with benzodiazepine as an adjunct medication to turn down hyperactivity of the NE system). [114] In contrast, in treating chronic stress-induced anxious depression, a facilitation of NE and/or 5-HT functioning (e.g., the use of NRI and SNRI) would be beneficial to normalize NE hypoactivity and this is not associated with exacerbation of anxiety symptoms (Fig. 3).…”
Section: Treatment Implications Of Ne System Dysregulationmentioning
confidence: 99%
“…Venlafaxine is recommended by the VA/DOD CPG [12] as a first-line treatment for PTSD. Venlafaxine's effectiveness for the treatment of PTSD was demonstrated in a large (N = 329) multinational RCT (Davidson et al [90]). Sleep quality measures were not reported in this study.…”
Section: Antidepressant Agentsmentioning
confidence: 99%